2022
DOI: 10.3390/molecules27061793
|View full text |Cite
|
Sign up to set email alerts
|

Computational Screening of Phenylamino-Phenoxy-Quinoline Derivatives against the Main Protease of SARS-CoV-2 Using Molecular Docking and the ONIOM Method

Abstract: In the search for new anti-HIV-1 agents, two forms of phenylamino-phenoxy-quinoline derivatives have been synthesized, namely, 2-phenylamino-4-phenoxy-quinoline and 6-phenylamino-4-phenoxy-quinoline. In this study, the binding interactions of phenylamino-phenoxy-quinoline derivatives and six commercially available drugs (hydroxychloroquine, ritonavir, remdesivir, S-217622, N3, and PF-07321332) with severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) main protease (Mpro) were investigated using molecul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“… Target Molecular docking software Binding affinity Kcal/mol Hydrogen bond with Ref 6M71 Autodock Vina -9 ASN781, HIS133, SER709, TYR129 LYS A47, ASP711 [156] 6M71 Autodock Vina − 8 LYS47, TYR129, SER709, ASP711, ASN781 [146] 6M71 Autodock Vina − 7.1 Lys621, Cys622, Asp761, Lys798, Glu811. [157] 7VH8 AutoDock 4.2 -8.56 GLY143 CYS145 LEU167 TYR54 CYS145 GLU166 [158] 6M71 AutoDock Vina -7.8 Gly143, Ser144 (2), Cys145, Glu166, Asn142 [159] 7BV2 AutoDockVina -7.2 ILE23, LEU126, GLY48 [160] 7BTF DOCK 6 -8.8 ALA 550, LYS 55, ARG 55, CYS 813, SER814, GLN 815 [161] Legend: ASN, asparagine; HIS, histidine; SER, serine; TYR, tyrosine; LYS, lysine; ASP, aspartic acid; ALA, alanine; ARG, arginine; CYS, cysteine; GLN, glutamine; GLY, glycine; LEU, leucine; GLU, glutamic acid; ILE, isoleucine. …”
Section: Targeted Proteins Using In Silico Methodsmentioning
confidence: 99%
“… Target Molecular docking software Binding affinity Kcal/mol Hydrogen bond with Ref 6M71 Autodock Vina -9 ASN781, HIS133, SER709, TYR129 LYS A47, ASP711 [156] 6M71 Autodock Vina − 8 LYS47, TYR129, SER709, ASP711, ASN781 [146] 6M71 Autodock Vina − 7.1 Lys621, Cys622, Asp761, Lys798, Glu811. [157] 7VH8 AutoDock 4.2 -8.56 GLY143 CYS145 LEU167 TYR54 CYS145 GLU166 [158] 6M71 AutoDock Vina -7.8 Gly143, Ser144 (2), Cys145, Glu166, Asn142 [159] 7BV2 AutoDockVina -7.2 ILE23, LEU126, GLY48 [160] 7BTF DOCK 6 -8.8 ALA 550, LYS 55, ARG 55, CYS 813, SER814, GLN 815 [161] Legend: ASN, asparagine; HIS, histidine; SER, serine; TYR, tyrosine; LYS, lysine; ASP, aspartic acid; ALA, alanine; ARG, arginine; CYS, cysteine; GLN, glutamine; GLY, glycine; LEU, leucine; GLU, glutamic acid; ILE, isoleucine. …”
Section: Targeted Proteins Using In Silico Methodsmentioning
confidence: 99%
“…Therefore, docking research that considers N3 as a standard for validating their docking protocols prior to a virtual-screening campaign should make use of one of the two approaches to docking covalent systems. Unfortunately, this has not been the case for several retrospective computational studies where noncovalent interactions of N3 with the Mpro target (6LU7) have been reported [ 107 116 ].
Fig.
…”
Section: Erroneous Drug Discovery Docking Pursuits Involving Covalent...mentioning
confidence: 99%
“…Quinoline, a fused structure of benzene and pyridine at adjacent carbon atoms, is a major pharmacophore system among nitrogencontaining heterocycles that have received renewed attention in the drug discovery field due to its intriguing pharmacological profile and fascinating biological properties. Both naturally occurring and synthetic derivatives of quinoline are critical in achieving important tasks and serving as an active ingredient in various medicines, including anticancer, [1] antimalarial, [2] antitubercular, [3] antiviral, [4] antibacterial, [5] antifungal, [6] anticonvulsant, [7] and anti-inflammatory. [8] Quinoline has been recognized as a promising starting point for developing drugs to combat Alzheimer's disease (AD) with several hybrid compounds, including 1,2-dihydroquinoline-3-carboxamides linked benzylpiperidines (3a, 3b), [9] quinoline-thiosemicarbazone (1a, 1b), [10] hydroxyquinoline analogs containing piperidine ring (2a) [11] have demonstrated strong anti-Alzheimer's activity.…”
Section: Introductionmentioning
confidence: 99%